2016
DOI: 10.1080/14737175.2016.1184572
|View full text |Cite
|
Sign up to set email alerts
|

Radionecrosis after stereotactic radiotherapy for brain metastases

Abstract: Our aim is to discuss the results of original studies on RN related to SRT for brain metastases. Expert commentary: Although the development of RN is unpredictable, larger volume of the lesion, prior whole brain irradiation, and higher dose of radiation represent the major risk factors. RN appears on MRI as contrast-enhancing necrotic lesions, surrounded by edema, occurring at least 3 months after SRT, localized within fields of irradiation. No firm criteria are established. Surgery can provide symptomatic rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 100 publications
1
70
2
2
Order By: Relevance
“…The most commonly reported AEs in both groups was radiation necrosis (RN) with an incidence of 50% and 28.6%, for both T-DM1 during treatment and T-DM1 discontinued before SRS, respectively. Therefore, the combination of T-DM1 with SRS induced a clinically relevant increase in the risk of RN, when compared to previously published data [38][39][40]. Moreover, Carlson et al [40] found an association with cerebral swelling in patients on T-DM1 who underwent SRS.…”
Section: T-dm1 and Stereotactic Radiosurgerymentioning
confidence: 60%
“…The most commonly reported AEs in both groups was radiation necrosis (RN) with an incidence of 50% and 28.6%, for both T-DM1 during treatment and T-DM1 discontinued before SRS, respectively. Therefore, the combination of T-DM1 with SRS induced a clinically relevant increase in the risk of RN, when compared to previously published data [38][39][40]. Moreover, Carlson et al [40] found an association with cerebral swelling in patients on T-DM1 who underwent SRS.…”
Section: T-dm1 and Stereotactic Radiosurgerymentioning
confidence: 60%
“…Radiation is targeted to the entire brain (whole brain radiation therapy, WBRT) or to a specific area of the brain (stereotactic radiotherapy). Though radiation may cause potential side effects such as cognitive impairment and radionecrosis of exposed brain tissue, resection followed by WBRT offers acceptable control of local disease (64). Treatment planning depends on the size, location, and number of metastases.…”
Section: Implications For Therapeuticsmentioning
confidence: 99%
“…30 Recent data suggests that RN rates may be increased in patients who receive concomitant immunotherapy with SRS. 31 …”
Section: Radiation Therapymentioning
confidence: 99%